Stará Ľubovňa – Lesopark. Late Palaeolithic site and the problems associated with raw material mining - Wawrzczak, Maciej; Kasenčáková, Zuzana (Dissertationes Archaeologicae, 2021)
A new archaeological site was discovered accidentally in year 2018. A surface survey revealed stone artefacts, which were generally dated to the Late Palaeolithic. Later, archaeological sondages were opened and newly found stone artifacts proved earliest dating. Furthermore, it was confirmed that local radiolarites were exploited by Late Palaeolithic societies.